Analysis of Damage to Shipping Container Sides During Port Handling Operations - Sergej Jakovlev; Tomas Eglynas; Valdas Jankunas; Mindaugas Jusis; Miroslav Voznak (Journal of Marine Science and Engineering)
The damage to shipping containers during port handling operations continues to pose a significant challenge that adversely affects operational efficiency, equipment integrity, and supply chain accountability. This study utilises real-world measurement data gathered through accelerometers to examine the occurrence and dynamics of physical impacts, particularly side and rear collisions, during the handling of containers at Klaipėda City Port. The research prioritises two critical scenarios: side impacts during stacking operations with reach stackers and rear impacts during trailer loading procedures. Impact events are meticulously recorded and analysed to ascertain the magnitudes of acceleration across multiple axes. This reveals that side impacts produce significantly greater forces, particularly in the lateral direction, than rear impacts. This study employs sensor-based monitoring, advanced data visualisation techniques, and structured scenario analysis to delineate the variability and intensity of mechanical interactions during these operations. The findings emphasise the structural stress that containers experience and underscore the importance of embedded monitoring technologies for real-time event detection and damage prevention. The results contribute to the expanding body of knowledge that supports the digital transformation of container terminals and furnish actionable insights for enhancing handling protocols, informing insurance assessments, and improving safety measures within both automated and conventional port environments.